Methodologies to assess muscle co-contraction during gait in people with neurological impairment: a systematic literature review - Rosa, Marlene (2018)
To review the methodologies used to assess muscle co-contraction (MCo) with surface electromyography (sEMG) during gait in people with neurological impairment. Methods The Scopus (1995–2013), Web of Science (1970–2013), PubMed (1948-2013) and B-on (1999–2013) databases were searched. Articles were included when sEMG was used to assess MCo during gait in people with impairment due to central nervous system disorders (CNS). Results Nineteen articles met the inclusion criteria and most studied people with cerebral palsy and stroke. No consensus was identified for gait assessment protocols (surfaces, speed, distance), sEMG acquisition (electrodes position), analysis of sEMG data (filters, normalisation techniques) and quantification of MCo (agonist-antagonist linear envelopes overlapping or agonist-antagonist overlapping periods of muscles activity, onset delimited). Conclusion Given the wide range of methodologies employed, it is not possible to recommend the most appropriate for assessing MCo. Researchers should adopt recognized standards in future work. This is needed before consensus about the role that MCo plays in gait impairment in neurological diseases and its potential as a target for gait rehabilitation can be determined.